Piscine reovirus in wild and farmed salmonids in British Columbia, Canada: 1974–2013. Issue 8 (22nd July 2014) - Marty, G D; Morrison, D B; Bidulka, J; Joseph, T; Siah, A
Abstract Piscine reovirus (PRV) was common among wild and farmed salmonids in British Columbia, western Canada, from 1987 to 2013. Salmonid tissues tested for PRV by real‐time rRT‐PCR included sections from archived paraffin blocks from 1974 to 2008 (n = 363) and fresh‐frozen hearts from 2013 (n = 916). The earliest PRV‐positive sample was from a wild‐source steelhead trout, Oncorhynchus mykiss (Walbaum), from 1977. By histopathology (n = 404), no fish had lesions diagnostic for heart and skeletal muscle inflammation (HSMI). In some groups, lymphohistiocytic endocarditis affected a greater proportion of fish with PRV than fish without PRV, but the range of Ct values among affected fish was within the range of Ct values among unaffected fish. Also, fish with the lowest PRV Ct values (18.4–21.7) lacked endocarditis or any other consistent lesion. From 1987 to 1994, the proportion of PRV positives was not significantly different between farmed Atlantic salmon, Salmo salar L. (44% of 48), and wild‐source salmonids (31% of 45). In 2013, the proportion of PRV positives was not significantly different between wild coho salmon, Oncorhynchus kisutch (Walbaum), sampled from British Columbia (5.0% of 60) or the reference region, Alaska, USA (10% of 58).